Deeply Odd [compact disc, unabridged] : an Odd Thomas novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2013)
In a sinister encounter with a rogue truck driver tricked up like a rhinestone cowboy, Odd has a disturbing vision of a shocking multiple homicide that has not yet been committed. Across California, into Nevada, and back again, Odd embarks on a riveting road chase to prevent the tragedy. Along the way, he meetsand charms a collection of eccentrics who become his allies in a terrifying battle against a sociopath of singular boldness and cleverness--and a shadowy network of mysterious, like-minded murderers whose chilling resources seem almost supernatural.